Assessment of pretreatment sludge profile in Istanbul metropolitan area. (21st July 2009) - Olmez-Hanci, Tugba; Kabdasli, Isik; Tunay, Olcay; Kinaci, Cumali
In this paper, the results of a comprehensive study on Istanbul's industrial pretreatment sludges are presented. 1042 industrial plants were applying pretreatment in Istanbul. The information gathered from several sources and site visits. Evaluation of the data, together with theoretical predictions indicated that total amount of pretreatment sludge was 100 tons per day on a dry matter basis. Approximately 90% of the sludge was produced in the European side of the city. 10% of the sludge originated from biological treatment. The results of the study were evaluated considering several factors such as origin of treatment, amount by subcategory and distribution by location.